Management of Sjögren's Syndrome: Present Issues and Future Perspectives - Vitali, Claudio; Minniti, Antonina; Pignataro, Francesca; Maglione, Wanda; Del Papa, Nicoletta (Frontiers in Medicine, 2021)
In view of the new possibilities for the treatment of primary Sjögren’s syndrome (pSS) given by the availability of new biotechnological agents targeting the various molecular and cellular actors of the pathological process of the disease, classification criteria aimed at selecting patients to be enrolled in therapeutic trials, and validated outcome measures to be used as response criteria to these new therapies, have been developed and validated in the last decades. Unfortunately, the therapeutic trials so far completed with these new treatments have yielded unsatisfactory or only partially positive results. The main issues that have been evoked to justify the poor results of the new therapeutic attempts are: (i) the extreme variability of the disease phenotypes of the patients enrolled in the trials, which are dependent on different underlying patterns of biological mechanisms, (ii) the fact that the disease has a long indolent course, and that most of the enrolled patients might already have irreversible clinical features. The advances in the research of new disease biomarkers that can better distinguish the different clinical phenotypes of patients and diagnose the disease in an earlier phase are also discussed.